Aristolochic acid induces an inflammatory response with prostaglandin E2 production and apoptosis in NRK-52E proximal tubular cells. (1st April 2023) - Komatsu, Miyu; Funakoshi, Takeshi; Aki, Toshihiko; Unuma, Kana; Uemura, Koichi
Abstract: Aristolochic acid nephropathy (AAN) is a type of drug-induced nephropathy in which ingestion of aristolochic acid (AA) causes acute kidney injury, with progressive renal fibrosis and upper urothelial carcinoma. Although the pathological features of AAN have been reported to involve significant cell degeneration and loss in the proximal tubules, the details of the toxic mechanism in the acute phase of the disease remain unclear. This study investigates the cell death pathway and intracellular metabolic kinetics of AA exposure in rat NRK-52E proximal tubular cells. AA exposure induces dose- and time-dependent apoptotic cell death in NRK-52E cells. We examined the inflammatory response to further investigate the mechanism of AA-induced toxicity. AA exposure increased the gene expression of inflammatory cytokines IL-6 and TNF-α, suggesting that AA exposure induces inflammation. Furthermore, analysis of lipid mediators by LC-MS revealed increases in intra- and extra-cellular arachidonic acid and prostaglandin E2 (PGE2). To investigate the relationship between the AA-induced increase in PGE2 production and cell death, celecoxib, an inhibitor of cyclooxygenase-2 (COX-2), which is involved in the production of PGE2, was administered, and a marked inhibition of AA-induced cell death was observed. These results suggest that exposure to AA induces concentration- and time-dependent apoptosis in NRK-52E cells, which is attributed to inflammatory responses mediated by COX-2 and PGE2. Highlights: Aristolochic acid (AA) induces concentration-dependent cytotoxicity in NRK-52E proximal tubular cells. AA induces the production of prostaglandin E2 via the arachidonic acid cascade, which induces an inflammatory response. Inhibition of prostaglandin E2 production by COX-2 inhibitors reduces AA-induced cytotoxicity.